Underwater acoustic communications based on differential chaos shift keying - Hongying DAI; Menglei CHEN; Weikai XU (Dianxin kexue)
As the most stringent and complicated channel,underwater acoustic (UWA) channels are featured by high multipath interference,time-frequency doubly spread,high noise,and narrow bandwidth.Due to time varying of underwater acoustic,it is difficult to trance and estimate channel state information (CSI).The underwater acoustic communication techniques based on orthogonal frequency division multiplex (OFDM) and spread spectrum were reviewed.Then,the characteristic of differential chaos shift keying (DCSK) was analyzed,and two multicarrier differential chaos shift keying modulations were proposed.Finally,over time-frequency doubly spread channel and underwater acoustic channel,the bit errors rate (BER) performances for two proposed schemes were presented and analyzed.Numerical results show that the proposed schemes own good robustness over underwater acoustic channels.